Development of young grafted walnut plants in nursery - Paunović, Svetlana; Miletić, Rade; Mitrović, Milisav (Economics of Agriculture, 2010)
The effect of a loamy alluvial soil deposit on the survival and growth of young grafted walnut plants was evaluated. The study was conducted during 2003-2005, involving one cultivar and four selections: Šeinovo (control), Ovčar, G-286, Elit and G-139. The survival percentage for the cultivar and selections at the end of the frst and second growing seasons was 77. 3% and 74. 3% respectively. The average vegetative growth of walnut nursery plants was 14.3 cm at the end of the frst year and 171.6 cm at the end of the second. The highest survival percentage at the end of the frst and second growing seasons was obtained in cv. Šeinovo (85. 3% and 82. 3%) and the lowest in G-139 (73. 4% and 70. 2% respectively). Vegetative growth at the end of the frst and second growing seasons was highest in G-286 (15. 0 cm) and cv. Šeinovo (177. 6 cm), respectively, and lowest in Elit, being 13. 6 cm at the end of the frst season and 165.5 cm at the end of the second.